2022
DOI: 10.3389/fgene.2022.919031
|View full text |Cite
|
Sign up to set email alerts
|

Association Between C-Reactive Protein and Risk of Amyotrophic Lateral Sclerosis: A Mendelian Randomization Study

Abstract: Background: Until now, the relationship between C-reactive protein (CRP) levels and amyotrophic lateral sclerosis (ALS) risk has not been fully established. It is necessary to assess whether there is a causal relationship between C-reactive protein levels and ALS risk.Objective and Methods: We aimed to determine whether CRP has causal effects on risk of ALS. In this present study, summary-level data for ALS (20,806 cases and 59,804 controls) was obtained from large analyses of genome-wide association studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Meanwhile, the elevation of CRP may reflect a neuroinflammatory state potentially responsive to the immune regulators 66 . Despite the important role of CRP in ALS, our study found no predictive power of CRP in ALS incidence, which was consistent with the previous mendelian randomization analysis 67 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, the elevation of CRP may reflect a neuroinflammatory state potentially responsive to the immune regulators 66 . Despite the important role of CRP in ALS, our study found no predictive power of CRP in ALS incidence, which was consistent with the previous mendelian randomization analysis 67 …”
Section: Discussionsupporting
confidence: 88%
“…66 Despite the important role of CRP in ALS, our study found no predictive power of CRP in ALS incidence, which was consistent with the previous mendelian randomization analysis. 67 Research on neutrophils in ALS remains at the tip of the iceberg, and many fields remain to be explored. First, neutrophil depletion has been shown to improve cognition in mice with Alzheimer's disease, 68 but its role in ALS has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in JAMA found that patients with ALS with elevated serum CRP levels progressed more rapidly than those with lower CRP levels [9], suggesting that serum CRP could serve as a prognostic biomarker for ALS. A subsequent study analyzing the association between serum CRP and ALS concluded that CRP was not associated with ALS survival [5], suggesting that CRP is not a risk factor for ALS [81]. In our analysis, serum CRP was not associated with RABGGTB level, ALSFRS-R score, or ∆FS, indicating that serum CRP may be a useful prognostic biomarker for ALS; however, multicenter and multiregional validation are required.…”
Section: Discussioncontrasting
confidence: 45%
“…A recent systematic review on Amyotrophic Lateral Sclerosis (ALS) concluded that CRP seems to be a promising prognostic biomarker, but extensive cohort studies are required to evaluate its prognostic value and accuracy; and a study proved that CRP was as a prognostic biomarker of ALS (elevated CRP > 2 mg/L), yet a Mendelian randomization study concluded that genetically predicted CRP levels may not be an ALS causal risk factor [ 575 , 576 , 577 ]. Except for the relation of CRP and age-related cognitive impairment, it was previously discussed that mCRP can possibly induce the cellular pathology of Alzheimer’s Disease (AD); nevertheless, data on AD seem controversial since a large study and a Mendelian randomization revealed a causal association between genetically elevated CRP and reduced risk for AD, while another study reported that genetically predicted increased CRP may be a causal risk for AD [ 578 , 579 , 580 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%